2018
DOI: 10.18632/aging.101383
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A irradiation induces senescence in human dermal fibroblasts by down-regulating DNMT1 via ZEB1

Abstract: In this study, we report the role of DNA methyltransferase 1 (DNMT1) in ultraviolet A (UVA)-induced senescence in human dermal fibroblasts (HDFs). We show that DNMT1 expression was significantly reduced during UVA-induced senescence, and this senescence could be alleviated or aggravated by the up- or down-regulation of DNMT1, respectively. Expression of the transcription factor zinc finger E-box binding homeobox 1(ZEB1) also decreased after UVA irradiation, following a UVA-induced increase of intracellular rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Particularly in untreated skin, this increase was striking, because normal epidermis displayed no detectable p16Ink4a expression, as observed also by others (21). Also the reduction of DNMT1 protein can be considered as a senescence marker as DNMT1 protein is decreased in senescent fibroblasts (11,22,23) and mouse keratinocytes (as previously discussed). Moreover, the inhibition of DNMT1 promotes senescence in these cells (11, 22, 23, s.a.).…”
Section: Discussionsupporting
confidence: 68%
“…Particularly in untreated skin, this increase was striking, because normal epidermis displayed no detectable p16Ink4a expression, as observed also by others (21). Also the reduction of DNMT1 protein can be considered as a senescence marker as DNMT1 protein is decreased in senescent fibroblasts (11,22,23) and mouse keratinocytes (as previously discussed). Moreover, the inhibition of DNMT1 promotes senescence in these cells (11, 22, 23, s.a.).…”
Section: Discussionsupporting
confidence: 68%
“…In support of this data interpretation, we found the upregulation of the oxidative phosphorylation enzymes in both types of analyses (Tables 3A and 3B ), and the hallmarks of reactive oxygen species pathways and peroxisome associated with ZEB1 HD class (Table 3A ). This is of particular interest as ZEB1 is indeed involved in ROS-induced cellular response as a crucial target of the miR-200 family members that are upregulated under oxidative stress conditions 37 41 .…”
Section: Resultsmentioning
confidence: 99%
“…We and other research groups have demonstrated that chronic repetitive UVA radiation as well as a single high dose of UVA radiation causes cellular senescence in vitro and contributes to the induction of skin photo-aging in vivo, mostly by the generation of ROS [19,29], particularly H 2 O 2 , which has a long half-life compared with O 2 − and 1 O 2 . To induce biological reactions in the skin, UVA radiation is absorbed by molecules, called endogenous and exogenous chromophores, such as flavins, porphyrins, pterins, urocanic acid, FICZ, heme-oxygenase-1, and NADPH-oxidase.…”
Section: Discussionmentioning
confidence: 97%